El flujo de caja en las empresas comerciales de la ciudad de babahoyo su utilidad como herramienta financiera para la obtención de créditos en el sistema financiero local - Real Maldonado, Silvia Eugenia (2009)
The communities in general move based on the strength of the society that are part of them, but above all because of the commercial factor, the commerce, being the exchange of goods and services, makes these communities overcome barriers and every day they grow and develop, in the city of Babahoyo, we see that, every day there is a greater proliferation of companies engaged in the trade of goods, compared to the few financial organizations that exist in this same community and that by this condition restrict the delivery of the credits, in front of that we propose a solution that allows on the basis of the adequate presentation of a basic financial document, as a tool of analysis and projection of benets, allowing this large development sector to have access to financial credits.